2011
DOI: 10.1177/1091142111423019
|View full text |Cite
|
Sign up to set email alerts
|

The Unemployment Puzzle of Corporate Taxation

Abstract: Using annual data on nineteen industrial countries for the period 1979–2005 and a large number of controls, this article is the first to empirically study the impact of corporate taxes on the unemployment rate. In contrast to previous empirical research on the labor demand, investment and growth effects of corporate taxation, which consistently finds adverse effects, the regression results suggest that higher corporate taxes may have a favorable impact, lowering the unemployment rate. The magnitude of the esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The main variable of interest, EATR is highly significant and implies that for a 1% raise in the tax rate, unemployment is expected to rise by 0.4%, which is a large effect not fully captured by the fixed effects or the OLS model. This result directly contradicts the results of the other main study using a Feldmann (2011). Looking at the tests provided, the only problematic result is the Sargan test, but, as mentioned earlier, this test is unreliable under the conditions of heteroscedasticity that is expected to be severe due to structural governmental differences between countries.…”
Section: Variables and Datamentioning
confidence: 71%
See 2 more Smart Citations
“…The main variable of interest, EATR is highly significant and implies that for a 1% raise in the tax rate, unemployment is expected to rise by 0.4%, which is a large effect not fully captured by the fixed effects or the OLS model. This result directly contradicts the results of the other main study using a Feldmann (2011). Looking at the tests provided, the only problematic result is the Sargan test, but, as mentioned earlier, this test is unreliable under the conditions of heteroscedasticity that is expected to be severe due to structural governmental differences between countries.…”
Section: Variables and Datamentioning
confidence: 71%
“…This dummy should account for the theoretically dampening effect of free labour movement on unemployment rates. While there are a host of other control variables mentioned in the literature that could have also been included, which are used by Feldmann (2011), the use of system GMM imposes restrictions on the number of variables which may be included in the regression. The inclusion of each new variable requires that lags of the variable also be included into the instrument set.…”
Section: Variables and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This belief is only valid in the model if flki>0. However, empirical evidence on the relation of employment to the corporate tax rate is controversial: Feld and Kirchgassner (2002), Bettendorf et al (2009), and Zirgulis and Sarapovas (2017) found that a rise in the corporate tax rate significantly increased unemployment levels while Feldmann (2011) showed that higher corporate taxes may lower the unemployment rate. Hence, we need to consider both possibilities in the analysis below.…”
Section: The Basic Modelmentioning
confidence: 99%
“…The motivation for the tax reforms in OECD countries was the promotion of investment and employment via reductions in the corporate income tax rate, and many of the countries that lowered the tax rate did so via a series of cuts over several years (OECD, 2017). The reforms are supported by empirical evidence which shows that the corporate income tax rate affects the employment rate (e.g., Feld & Kirchgassner, 2002; Feldmann, 2011).…”
Section: Introductionmentioning
confidence: 99%